Think tanks and the politics of climate change - Dieter Plehwe (Handbook on Think Tanks in Public Policy, 2021)
In deliberation-minded and civil society-oriented scholarship, think tanks are relevant because of their constructive role in policy-related knowledge generation. They are held to establish and enable expertise from diverse stakeholders and multiple angles, and to successfully feed the policy process. The environmental policy field, in general, and climate change mitigation especially, allows additionally for the observation of a less benign and wider range of roles and functions for think tanks across multiple conflict constellations. Conflict theoretical and power-sensitive approaches implicate the need to relate think tanks – in agnostic ways – to the political struggles of competing discourse coalitions that frequently rely on problem-solving research, as well as destructive strategies of `knowledge shaping' and `strategic ignorance'. The current vitriol in climate change mitigation debates cannot simply be attributed to the abuse of science and fake news. Evidence points to a far-ranging transformation of the `global knowledge power structure' in which policy think tanks have come to play an increasingly important and ambiguous role.
Keywords: 300; think tanks; networks; climate change; governance; conflict; neoliberalism; discourse coalition